PENGARUH PROMOTIONS MIX TERHADAP KEPUTUSAN MENGINAP TAMU DI HOTEL SANTIKA PREMIERE SLIPI, JAKARTA - Runi Yulianti Togubu (Program Studi Hospitality dan Pariwisata, 2022)
Researchers want to examine the effect of the promotion mix on the decision to stay at the Santika Premiere Slipi Jakarta. The results of multiple linear regression analysis show that advertising has no significant effect on the decision to stay, then sales promotion, personal selling, public relations, and direct marketing have a significant effect on the decision to stay. This can be shown by Fcount of 124.830 with Fcount probability of0.000 < 0.05. The amount of the contribution of the 5 independent variables together to the decision to stay is 62.2%. While 37.8% is influenced by other variables that are not tested by this study. This study shows that individually the four variables, namely sales promotion, personal selling, public relations, and direct marketing have a significant influence on the decision to stay, only advertising has no significant effect on the decision to stay. The results of this study indicate that direct marketing is the most dominant influence on the decision to stay.